The dependence of tree pollen production on the weather conditions in the south of West Siberia - Lukanina, Ekaterina; Blyakharchuk, Tatiana (Ecological Questions, 2017)
In the present study, we have investigated the dependence of the composition of the modern spore and pollen spectra on the composition of the vegetation cover in the southern part of Western Siberia (south of the Tomsk region) using the Tauber traps. We also found out the correlation between the spore and pollen spectra and the weather conditions of the year under study.